Comparitive Study of Cognitive Development of Students of Different School Systems in Pakistan - Durrani, Dr.Rukhsana; Rasheed Choudhary, Farkhunda (Journal of Peace, Development and Communication, 2021)
This study was conducted to explore the cognitive development of students of Madaris, public sectors and private sectors of Islamabad. It was quantitative research. A sample of 716 students was selected randomly from three streams of education. To measure the cognitive development of students, a standardized tool was used to collect data. The tests were administered, scored, and was analyzed through SPSS. Results showed a significant difference among cognitive development of students of three educational systems. Analysis of the data showed a significant difference among scores in subtests i.e. analogies, the odd one out, and similarities. Similarly, students of the private sector had better overall means scores than the mean score of students of Madaris and public schools. As the three systems claim for development of cognitive abilities of students therefore it is recommended that the curriculum, teaching methodologies and learning resources of the three systems may be compared and streamline them for harmonious cognitive abilities of students.